ACCOUNTABILITY IN SHARIA SERVICE BUSINESS PRACTICES WITHIN THE LOCAL ECONOMY: AN ETHNOMETHODOLOGICAL STUDY IN MALANG - Arista Fauzi Kartika Sari; Nuril Badria (Academic Bright Collaboration, 2026)
This research aims to examine how local sharia service businesses construct and practice accountability beyond merely using Islamic branding. Many local economies have adopted Islamic branding for their service businesses, yet a gap often remains between their claims and operational practices. Islamic branding should not function only as a market-oriented label but should substantively integrate Islamic values into daily operations. This qualitative study employs an ethnomethodological approach. The analysis focuses on three core concepts: indexicality, reflexivity, and common-sense knowledge. Data were collected through direct observation, semi-structured interviews, and documentation. Interviews were conducted with owners and staff of a Sharia laundry, a Sharia travel agency, and a sharia guest house in Malang, Indonesia. The indexicality of Sharia laundry is the purification of clothes at the end of the washing process (thaharah). Sharia travel is collaborating with halal-certified restaurants and Sharia guest houses. Sharia guest houses ensures that guests are mahram and collaborate with sharia laundries. Reflexivity among all respondents indicates that the operational practices of these three businesses reflect a commitment to Sharia principles. Common-sense knowledge such as the local understanding that purification is using running water, halal sign on a restaurant guarantess safety, and staying overnight together with someone who is not mahram is forbidden The synergy between Islamic branding and local economic practices can help build public trust and support the sustainability of Sharia businesses. However, this study is limited because it does not include formal compliance confirmation from the DSN-MUI (Indonesian Ulema Council). Findings are also context‑specific and not generalizable. This study offers originality by applying ethnomethodology to examine accountability in Sharia service businesses within the local economy, a topic rarely explored in halal industry research. It demonstrates that sharia accountability is socially constructed rather than through formal certification alone.